Risk assessment method for power grid communication link failure based on fuzzy comprehensive assessment. Issue 2 (22nd June 2022) - Mo, Lianguang; Wei, Liang
In order to overcome the problems of long time and inaccurate evaluation results of traditional power grid communication link fault assessment methods, a new power grid communication link fault risk assessment algorithm based on fuzzy comprehensive evaluation is proposed. The fuzzy comprehensive evaluation method is used to comprehensively evaluate the risk of the power grid communication link. Based on the failure rate curve of the power grid failure rate model and the Weibull distribution function, a power grid communication link failure risk analysis model is established to complete the power grid communication link failure risk assessment. The experimental results show that compared with the existing risk assessment algorithms, the average assessment time is shortened by 17 seconds, the accuracy of the assessment results is increased by 7.9%, and the cost is reduced by 23.35%.